USE OF MODERN METHODS IN GERMAN LESSONS FOR TECHNICAL DISCIPLINES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In today's digital educational landscape, foreign language teaching, especially German teaching for technical disciplines, is becoming increasingly important. This scientific article examines the use of modern methods in the teaching process and analyzes their effectiveness in technical courses. Particular attention is paid to digital teaching and learning formats, interactive forms of teaching and didactic concepts based on technical language. The aim is to show ways in which both the language competence and the professional competence of learners can be improved through innovative methods.